Implementasi Strategi City Branding Dalam Meningkatkan Daya Saing Daerah Kota Malang - Kurniawan, Mohammad Rizky (Jurnal Administrasi Publik, 2014)
Abstract: Implementation Of City Branding Strategies In Improving The Competitiveness of Malang. This research was conducted by based on the importance of City Branding strategy implementation in improving the region competitiveness, the Government of Malang, represented by Department of Culture and Tourism of Malang did this City Branding  since endorsed by the mayor at Regent Hotel in 2006 under the name of Malang Welcoming City. How the implementation of City Branding strategy in enhancing Malang regional competitiveness and how it impacts the implementation of Malang City Branding strategy in improving Malang regional competitiveness. This study used descriptive method with qualitative approachment, and data analysis using Cresswell’s method. The results showed that the implementation of Malang City Branding strategy has not been maximized yet, even the public and members of the Malang government also have not been known about this City Branding Malang well. In addition, funding and management turnover were also being barriers in implementing the strategy for City Branding Malang. Keywords: implementation, strategies, city branding, competitiveness, Malang.   Abstrak: Implementasi Strategi City Branding dalam Meningkatkan Daya Saing Daerah Kota Malang. Penelitian ini dilakukan atas dasar pentingnya implementasi strategi City Branding dalam meningkatkan daya saing daerah, Pemerintah Kota Malang yang diwakili oleh Dinas Kebudayaan dan Pariwisata Kota Malang melakukan City Branding sejak disahkan oleh walikota di Hotel Regent pada tahun 2006 dengan nama Malang Welcoming City. Bagaimanakah implementasi strategi City Branding dalam meningkatkan daya saing daerah Kota Malang dan bagaimana dampak implementasi strategi City Branding Kota Malang dalam meningkatan daya saing daerah Kota Malang. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kualitatif, dan analisis data menggunakan metode analisis data Cresswell. Hasil penelitian menjelaskan bahwa implementasi strategi City Branding Kota Malang masih belum maksimal, masyarakat bahkan pegawai Pemerintah Kota Malang pun juga tidak mengetahui apa City Branding Kota Malang. Selain itu pendanaan dan juga pergantian kepengurusan juga menjadi faktor penghambat implementasi strategi City Branding Kota Malang.   Kata kunci: implementasi, strategi, city branding, daya saing, Kota Malang.